Experimental study of the effect of argon on the restrike characteristics of nitrogen arc. (1st September 2022) - Shao, Ke; Sun, Su-Rong; Meng, Xian; Huang, He-Ji; Hu, Ya-Hao; Wang, Hai-Xing
Abstract: The arc restrike process is a typical mode of operation within a direct current arc plasma torch. By using a transfer arc device with a planar anode parallel to the gas flow direction, the effect of argon addition on the disappearance of downstream old arc roots, the overall arc downstream movement process and the generation of upstream new arc roots of the nitrogen arc restrike process is experimentally investigated. The experimental results show that for pure nitrogen arc, the restrike frequency is very high and the old arc root disappears very quickly. The addition of argon will significantly decrease the temperature of the arc root and prolong the coexistence time of the old and new arc roots. This phenomenon is caused by the rapid decay of charged particle density in the nitrogen arc, because the recombination process of charged particles in the nitrogen arc is faster than that in the argon arc. The breakdown field strength at the upstream location where the new arc root occurs is calculated by combining the measurements of arc voltage, arc grayscale image and temperature. The results show that as the percentage of argon increases, the boundary layer thickness becomes thinner and the critical electric field strength required for arc breakdown decreases, leading to the generation of new arc roots more likely to occur toward the upstream location. This study improves the understanding of the effect of argon on the nitrogen arc restrike process.